Childcraft shapes and numbers (World Book, Inc Chicago, IL, 1979)
Vol. 1--Poems and Rhymes, Vol. 2-Once Upon a Time, Vol. 3--Art Around Us, Vol. 4--The World of Animals, Vol. 5--The World of Plants, Vol. 6--Our Earth, Vol. 7--The Universe, Vol. 8--How Does It Happen?, Vol. 9--How Things Work, Vol. 10--Shapes and Numbers, Vol. 11--About You, Vol. 12--Who We Are, Vol. 13--See the World, Vol. 14--Celebrate!, Vol. 15--Guide and Index